Biochemical disturbances in schizophrenia — a «window of opportunity» - T. V. Zhilyaeva; A. S. Piatoikina; E. D. Kasyanov; G. V. Rukavishnikov; I. V. Semennov; O. V. Kostina; A. S. Blagonravova; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
Introduction: Currently, there is a large amount of data that inflammatory and oxidative stress biomarkers, pterin metabolism disturbances and other biochemical abnormalities are more often present in schizophrenia compared to general population. They may also play the role of etiopathogenetic factors in schizophrenia mechanisms. At the same time, there are no studies with an assessment of a wide range of correctable biochemical abnormalities in one sample of patients. Moreover, screening algorithms for the detection and personalized correction of controlled biomarkers have not been introduced into clinical practice yet.   The aim of this work was to evaluate the prevalence of significant etiopathogenetic biochemical disturbances in patients with schizophrenia in order to justify the need for biochemical screening and correction of the corresponding abnormalities.   Materials and methods: in the blood serum of 125 patients with schizophrenia and 95 healthy volunteers the levels of folate and cobalamin (B12) (chemiluminescent immunoassay on microparticles), homocysteine (HC, enzymatic analysis), tetrahydrobiopterin (BH4, competitive enzyme immunoassay, ELISA), reduced glutathione (GSH, spectrophotometry with Ellman’s reagent), interleukin-6 (IL-6, ELISA based on a three-stage «sandwich version») and C-reactive protein (CRP, immunoturbodimetric method) were evaluated.   Results: In patients with schizophrenia the level of all studied serum biochemical markers, except for B12, was significantly different compared to healthy volunteers. The deviations levels of the studied parameters from the reference values in patients were statistically significantly higher in the markers of pterin metabolism (VH4: p = 0.0000; folates: p = 0.0000; HC: p = 0.0094). 29.6 % of patients were carriers of 4 or more studied biochemical abnormalities, while among healthy volunteers this occured in 5.3 % of cases (Xi2 = 19.2; p < 0.001).   Conclusion: The results obtained raise the question for the need of monitoring principles for a number of biochemical markers in schizophrenia and their implementation in clinical practice.